Consumers using social media: impact on companies’ reputation - Alturas, B.; Oliveira, L. (Proceedings of the Academy of Marketing Conference 2016: Radical Marketing, 2016)
This paper addresses the topic of the impact social networks on companies’ reputation. Before a consumer with new aptitudes, access to new technologies and, above all, to a wider and more dynamic range of alternative communication sources, companies must pay attention to all that is written about in social networks, and should be especially careful about what to publish and the answer they give to their customers' publications. Social networks have become, in recent time, one of the most developed, simple and accessible means of communication. Herewith, even more companies pay attention to their reputation because one simple comment or opinion about a product/service of a company/brand could influence the decision making of other users/consumers. With regard the work’s methodology, after a literature review, a questionnaire to the users/consumers was applied in order to analyse the use of social networks, the opinions transmitted and how the company’s reputation may get out impaired in order to raise awareness of the factors that can influence the reputation of companies on social networks. So it is important to plan and work effective business communication strategy in a radical marketing perspective.